2017
DOI: 10.7759/cureus.1411
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Health Promotion for Chinese Americans

Abstract: IntroductionThis study aims to describe the results of a dementia awareness campaign in the Chinese American community. MethodsThe campaign consisted of a health fair, four dementia seminars, radio shows, television episodes, and a YouTube series. Descriptive statistics and qualitative data were obtained from various health communication channels.   ResultsThere were 156 and 313 participants in the health fair and dementia seminars, respectively. The participants in each component of the campaign also provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
2
29
0
2
Order By: Relevance
“…20 One example utilised several methods such as health fairs, dementia seminars, radio shows, television episodes, and a YouTube series to disseminate information as a way to destigmatize dementia in a Chinese-American community. 29 An important finding from our study is the lack of culturally appropriate education around dementia for Asian New Zealanders, with a lack of resources in non-English languages. Jang et al reported similar findings in their survey of Korean immigrants in the USA in which less than 20% of participants had seen educational materials on dementia in Korean language.…”
Section: Implications For Policy and Practice In Nzmentioning
confidence: 88%
See 1 more Smart Citation
“…20 One example utilised several methods such as health fairs, dementia seminars, radio shows, television episodes, and a YouTube series to disseminate information as a way to destigmatize dementia in a Chinese-American community. 29 An important finding from our study is the lack of culturally appropriate education around dementia for Asian New Zealanders, with a lack of resources in non-English languages. Jang et al reported similar findings in their survey of Korean immigrants in the USA in which less than 20% of participants had seen educational materials on dementia in Korean language.…”
Section: Implications For Policy and Practice In Nzmentioning
confidence: 88%
“…There are relatively few research examples focusing on decreasing the stigma related to dementia in general or specifically for the Asian population . One example utilised several methods such as health fairs, dementia seminars, radio shows, television episodes, and a YouTube series to disseminate information as a way to destigmatize dementia in a Chinese‐American community …”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that although Chinese Americans hold misconceptions about dementia, their lack of knowledge does not reflect a lack of desire to become further educated about this medical condition [ 3 ]. Moreover, other recent studies have demonstrated that Chinese Americans are becoming more receptive to e-health and to obtaining dementia knowledge using the Internet than before [ 11 - 13 ]. In 2014, Google occupied 69% of the global search engine market and was the most popular search engine in the United States [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite comparable rates of mental health disorders and overall disease among Asian Americans and non-Hispanic whites, this study revealed that while 25.0% of hypertension health care was utilized by Asian Americans, they only accounted for 9.2%, 10.5%, 12.9%, 13.8%, and 14.7% of mental health service utilization for bipolar disorder, schizophrenia, anxiety, depression, and intellectual disabilities, respectively. Particularly for Asian Americans, stigma and other barriers can deter patients and their families from seeking needed mental health services [ 10 - 11 ]. In comparison with medical illnesses, the stigma surrounding psychiatric disorder contributes to shame in the Asian American community, which can affect both quality and access to care [ 12 - 13 ].…”
Section: Discussionmentioning
confidence: 99%